BAYANI EPISTEMOLOGIES IN MODERN INDONESIA: The Contribution of Al Washliyah Ulama to Quranic Exegesis Studies - Ja'far, Ja'far; Iqbal, Muhammad (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2023)
Abstract: The contribution of Islamic organizations in Quranic exegesis (tafsîr) in Indonesia has been largely overlooked by researchers. However, this study aims to explore this topic due to the significant influence of Islamic organizations on various aspects of Muslim life in the country. One such organization is Al Washliyah, the third largest Islamic organization in Indonesia, which has received limited attention from experts in terms of its contribution to the preservation and development of Quranic exegesis. This literature-based research adopts a historical approach, and the research topic is analyzed through Max Weber’s theories of social action and dominance of power. This study argues that Al Washliyah ulama have taught various books on Quranic exegesis in its madrasas, published articles on the Quran and its tafsir in its official magazine Medan Islam (also Dewan Islam), and its ulama have produced several works in the field of Quranic exegesis. Moreover, due to its adherence to the Ahl al-Sunnah wa al-Jamâ‘ah (Sunni) creed and the Shâfi‘iyah school of jurisprudence, Al Washliyah tends to disregard Quranic exegesis literature from other schools. This study, of course, contributes to the strengthening of literature on Quranic studies in modern Indonesia.Keywords: Quranic exegesis, Al Washliyah, madrasas, Islamic magazine, ulama